An integrated process for the production of 2, 5-dimethylfuran from fructose1. Issue 6 (8th June 2015) - Upare, Pravin P.; Hwang, Dong Won; Hwang, Young Kyu; Lee, U-Hwang; Hong, Do-Young; Chang, Jong-San
<x xml:space="preserve">Abstract</x> 2, 5-Dimethylfuran was produced in 92% yield from fructose in 1-butanol through a combination of dehydration over Amberlyst-15 and hydrogenolysis over Ru–Sn/ZnO.